THE INITIAL STAGES OF TEACHING A FORIGN LANGUAGE - Turakulova Nilufar Mamaraim’s, (Ustozlar uchun, 2025)
In this article ,all of generations can see that, modern teaching of  English Language ,useful methods and students’ difficult situations of  Learning  Forign Language .Then modern  Technologies and Communicative Methods will judged ,beneficial recommendations will given to students and other  young  generations.